Treatment Of Toilet Odor Using Horizontally Placed Odor Removal Membrane - Md.Nor, Nuramalina (Universiti Sains Malaysia, 2018)
Toilet is considered the most visited place in a home or in public. The frequency of the toilet being used and the activity conducted in it led to a bad condition where it can have offensive smell and the odorous condition of the toilet often be a concern towards its users. There are several methods applied in dealing with odor in the toilet such increasing the frequency of the toilet being washed, the application of fragrance and also a wise toilet’s ventilation design. This study that took place in toilet located in girl’s hostel at Desasiswa Lembaran, was conducted to focus on treatment of the toilet’s odor using odor removal membrane, which is Deodoratex. The odor control efficiency of the both type of Deodoratex fabrics, Type 03 and Type 32 that are used in this study are evaluated by measuring the odor unit concentration (OU/m³) and odor intensity in the toilet before and after the installation of the fabrics. The removal of ammonia and hydrogen sulfide also being measured and compared for both fabrics in both situation (before and after installation). Ammonia adsorption test also conducted on the fabrics to determine the capability of the fabrics to really adsorb ammonia concentration. Both fabrics shows a great odor control efficiency in the toilet even the odor intensity and odor character varies from time to time. These fabrics also have a positive values of odour removal efficiency where fabric Type 32 shows a greater percentage in removal of ammonia and hydrogen sulfide. In the ammonia adsorption test, the fabrics showed significant effects on ammonia gas as the concentration of ammonia after the test was lower compared to the concentration of untreated ammonia. Type 32 fabrics have higher amounts of ammonia-nitrogen when the washing water is tested using the Hach Spectrophotometer.